Repurposing piroxicam enhances the antineoplastic effects of docetaxel and enzalutamide in prostate cancer cells using 2D and 3D in vitro culture models - Yehya, Amani; Ghamlouche, Fatima; Karami, Raed; Hachem, Sana; Salhab, Zahraa; Liu, Yen-Nien; Daoud, Georges; Abou-Kheir, Wassim (Frontiers in Cell and Developmental Biology, 2025)
IntroductionDrug repurposing is gaining consideration in cancer due to the challenges of poor outcomes and resistance associated with the current conventional modalities. Non-steroidal anti-inflammatory drugs (NSAIDs), widely used for treating inflammation, are being explored for their potential efficacy in cancer treatment, including prostate cancer (PCa). This study aims to evaluate the efficacy of Piroxicam (PXM), an NSAID, in enhancing the sensitivity of PCa cells to chemotherapy and hormonal drugs.MethodsComputational analysis was conducted to identify differentially expressed genes between our established murine PCa cell models, PLum-AD (androgen-dependent) and PLum-AI (androgen-independent), to uncover potential therapeutic targets. In two-dimensional (2D) cell culture, cell proliferation, viability, and migration assays were performed on PLum-AD and PLum-AI cells treated with PXM alone or in combination with docetaxel (Doc) or enzalutamide (Enz). Additionally, the impact of these treatments on stem-like progenitor cells was assessed using three-dimensional (3D)-Matrigel™-based sphere-forming and organoid formation assays.ResultsTranscriptomic analysis revealed that inflammatory pathways are enriched during PCa progression, making them viable targets for NSAID-based interventions. Single treatment of PXM demonstrated significant anti-cancer effects on PLum-AD and PLum-AI cells, evidenced by reduced cell proliferation, viability, migration, sphere growth, and organoid growth.DiscussionImportantly, PXM treatment in combination with Doc or Enz resulted in more pronounced antineoplastic effects compared to single-drug exposure. Our work suggests PXM as a potential adjunctive therapy to enhance the efficacy of conventional treatments in PCa patients.